2019
DOI: 10.1371/journal.pone.0219534
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis clinical case definition: Time for change in developing countries?

Abstract: Background Developing countries still struggle with late detection and mortality from pertussis. A review of clinical case definitions is necessary for early disease detection. This paper aimed to study possible clinical characteristics for earlier pertussis detection in a sporadic setting. Methods We conducted a retrospective review of medical and laboratory records in a general paediatric ward of a district hospital in a developing country. Inclusion criteria were all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Current clinical case definitions for surveillance may miss cases early in the course of the disease and, as a matter of fact, a significant number of pertussis cases fulfilled the clinical case definition for surveillance only several days after the enrollment in this study. Specific algorithms, therefore, may help to improve early diagnosis even in low resource settings [25]. Moreover, the performance of case definitions is affected by the prevalence of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current clinical case definitions for surveillance may miss cases early in the course of the disease and, as a matter of fact, a significant number of pertussis cases fulfilled the clinical case definition for surveillance only several days after the enrollment in this study. Specific algorithms, therefore, may help to improve early diagnosis even in low resource settings [25]. Moreover, the performance of case definitions is affected by the prevalence of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…A possible change of pertussis case definition and duration of cough has long been debated [ 9 , 25 , 28 30 ]. To our knowledge, an algorithmic approach to refine pertussis case definitions and achieve a better performance has never been used, and deserves attention in perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Involving only suspected cases of pertussis to assess diagnostic accuracy of the same features on which the sample was selected has the potential of exaggerating the diagnostic accuracy of clinical criteria. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Considering that non-specific symptoms of pertussis constitute a mandatory notification of a suspected case of pertussis, it is possible that this procedure could introduce bias into the classification of pertussis cases. Moreover, several studies have shown a higher frequency of pertussis in children aged one year or less, mainly those under six months, who present high numbers of hospitalizations and more frequent disease complications [ 1 , 13 , 24 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, cure was the predominant outcome and no pertussis deaths were identified among the patients investigated during the study period. Indeed, the prognosis is generally good in most confirmed pertussis cases, with a typical mortality rate of around 2% [11,27,35].…”
Section: Plos Onementioning
confidence: 99%